Design and radiological study of the 225Ac medical target at the TRIUMF-ARIEL proton-target station. (November 2022) - Augusto, R.S.; Smith, J.; Varah, S.; Paley, W.; Egoriti, L.; McEwen, S.; Goodacre, T. Day; Mildenberger, J.; Gottberg, A.; Trudel, A.; Hoehr, C.
Abstract: At the Advanced Rare Isotope Laboratory (ARIEL) at TRIUMF, two targets will be irradiated in series with up to 100 µA of a 500 MeV proton beam. Whilst the upstream target will be used for radioactive ion beam production via the isotope separation on-line (ISOL) method, the downstream target will make use of the transmitted beam for medical isotope production, especially for targeted radiation therapy. The medical target design was optimized to meet both requirements for in-target   225 Ac production as well as to operate within the ARIEL proton station via FLUKA and ANSYS simulations. To host the medical target, a module was specially designed and integrated into the shielding envelope. In addition, three failure scenarios are also considered, featuring maximum credible incidents that highlight the overall shielding performance. An evaluation of the dosimetry impact throughout the final stage of the medical target life cycle was also carried out. The latter entailed the reproduction of residual ambient dose rates when a dismantled target is retrieved from the hotcell and sent for processing in a shielded container. Overall, the simulation work led to the validation of the medical target design and its operation within the scope of ARIEL. Highlights: Combined FLUKA and ANSYS studies to design a symbiotic target for   225 Ac production. Proton target station optimized to produce 8 batches with 15 GBq of   225 Ac annually. Mitigation of the radiological impact of the medical target and its infrastructure.